Is continuous training to re-skilling and up-skilling employees needed by companies? - Purwono, Prahoro Yudo (Jurnal Manajemen, 2024)
This study examines the necessity of continuous training through re-skilling and up-skilling for employees within Indonesian companies. As the global market evolves, technological advancements and changing business landscapes require firms to enhance their workforce capabilities to remain competitive. The research aims to elucidate whether ongoing professional development is crucial for organizational success in Indonesia. Utilizing both qualitative and quantitative approaches (percentage-based), the study integrates survey results on employee competency improvement needs and challenges with existing literature. The study's findings indicate a significant correlation between continuous training programs and enhanced employee performance and career development, which subsequently positively impact company progress. The conclusions drawn from this research emphasize the critical role of sustained training in empowering employees and driving business growth. Employees can develop their skills through training programs, which benefits the company.